Comparison of Performance of Stock and Sharia Stock - Kharisma Novita Sari; Debi Maenadi; Mimah Mutamimah; Maya Zulfa Maslihatin (Indonesian Economic Review, 2022)
The purpose of this study was to examine the differences in the performance of Islamic stocks with stocks based on the Sharpe and Jensen method for the 2010-2020 period in the Indonesian Capital Market. The research method is using a quantitative approach with the type of comparative research. The data used is secondary data from OJK. The population used in this study is the capitalization of sharia stock performance data compared to stocks, for the 2010-2020 period (monthly data) in the Indonesian Capital Market. Data analysis was carried out using the Sharpe and Jensen method and the Manova test with the help of the SPSS statistical program. The results of this study indicate that the performance of Islamic stocks with stocks has a significant difference and the performance of Islamic stocks is better than stocks based on the Sharpe and Jensen method. This shows that the return on the performance of sharia shares with shares based on the Sharpe and Jensen method that will be received will be relatively different. The implication of this research is that this research can contribute to the general public, both academics, investment players and the general public so that they better understand the performance of capital market investment instruments before they invest.